ANALISIS PENAWARAN CABE RAWIT (Capsicum frutescens L.) CHILI (Capsicum frutescens L.) SUPPLY ANALYSIS - Adi Ismanto; Febriyanti Ika Wulandari (Progresif : Media Publikasi Ilmiah, 2021)
This study aimed to determine the factors that affect the supply of chili and chili due to changes in the price of the supplied amount of chili. The data used are primary data obtained by observation and interviews directly to farmers chili. The analytical method used was multiple linear regression analysis and supply elasticity. Multiple linear regression analysis was used to determine whether there is the influence of the seed prices, fertilizer prices, the pesticide prices, and labor wages to supply chili. While the supply elasticity is used to determine the effect of price changes to changes in the amount of chili suplied. The results show the value of the adjusted R square of 0,497 means that independent variables such as the seed prices, fertilizer prices, the pesticide prices, and labor wages that can explain the variation of chili supply of 49,7%. While the remaining 50,3% is explained by other causes. F is obtained from F test count of 8,161 with a significance level of 0,000, meaning that the seed prices, fertilizer prices, the pesticide prices, and labor wages jointly significant effect on chili deals. t test results indicate that the variable the seed prices and fertilizer prices effect is not significant to supply chili. While the variable the pesticide prices and labor wages significantly affect chili supply. Price changes positively and chili is elastic to changes in the amount of chili supplied.